Penerimaan Pluralitas Agama sebagai Syarat Kemungkinan Etika Politik - Author: Haryatmoko (Unisia, 2005)
Religion constitutes the place of peace, the life meaning, and it contains the optimistic goal of human, but (often in reality) it relates to violence phenomenon. The apology is usually declared that religion is actually right values, but the religious people justify their interests in the name of religion. The problem is can religion separate from the followers? So, socializing the ethical values and the acceptance of plurality do not only cognitive aspect, but also habit us meaning. Hence, to develop tolerance attitude, it is urgent to motivate, to educate children since child hood to have habit, involment experience and to communicate with different religion followers, for example paying attention to poor and marginalized people. This together living is the best way to build the possibility of political ethics.